PENGARUH MODEL COMMUNICATIVE LANGUAGE TEACHING (CLT) TERHADAP KEMAMPUAN MEMBACA DAN BERBICARA BAHASA INGGRIS SISWA KELAS VIII UPTD SMPN 2 SOCAH - Febrianto, Eddi; Muhajir; Silver, Soesiana Tri Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aims of this research are: 1) Proving the influence of the communicative language teaching model on the English reading ability of class VIII students at UPTD SMPN 2 Socah, 2) Proving the influence of the communicative language teaching model on the English speaking ability of class VIII students at UPTD SMPN 2 Socah, and 3) Proving the influence of the communicative language teaching model on the English reading and speaking abilities of class VIII UPTD SMPN 2 Socah students. This research is a quantitative experimental study where the research sample is 56 students consisting of 28 students from class VIII-A as the control group and 28 students from class VIII-B as the experimental group. The instruments of this research are reading ability test questions and speaking ability assessment sheets. Based on the results of data analysis using paired sample t test and MANOVA, it was concluded that: 1) There is an influence of the communicative language teaching model on the reading comprehension ability of class VIII students at UPTD SMPN 2 Socah, 2) There is an influence of the communicative language teaching model on the speaking ability of class VIII UPTD students. SMPN 2 Socah, and 3) There is an influence of the communicative language teaching model on the reading comprehension and speaking abilities of class VIII UPTD SMPN 2 Socah students.